Basic reproduction number (R0) of SARS-CoV-2 - Nuwan Darshana Wickramasinghe; Sumudu Hewage; Surangi Jayakody; Shamini Prathapan; Carukshi Arambepola (College of Community Physicians of Sri Lanka, 2020)
No abstract available